Bioprospecting of Soil-Derived Actinobacteria Along the Alar-Hotan Desert Highway in the Taklamakan Desert - Liu, Shaowei; Wang, Ting; Lu, Qinpei; Li, Feina; Wu, Gang; Jiang, Zhongke; Habden, Xugela; Liu, Lin; Zhang, Xiaolin; Lukianov, Dmitry A.; Osterman, Ilya A.; Sergiev, Petr V.; et al. (Frontiers in Microbiology, 2021)
Taklamakan desert is known as the largest dunefield in China and as the second largest shifting sand desert in the world. Although with long history and glorious culture, the Taklamakan desert remains largely unexplored and numerous microorganisms have not been harvested in culture or taxonomically identified yet. The main objective of this study is to explore the diversity, novelty and pharmacological potential of the cultivable actinomycetes from soil samples at various sites along the Alar-Hotan desert highway in the Taklamakan desert. A total of 590 actinobacterial strains were recovered by the culture-dependent approach. Phylogenetic analysis based on 16S rRNA gene sequences unveiled a significant level of actinobacterial diversity with 55 genera distributed in 27 families of 12 orders. Thirty-six strains showed relatively low 16S rRNA similarities (< 98.65%) with validly described species, among which 4 strains had already been characterized as novel taxa by our previous research. One hundred and forty-six actinobacterial isolates were selected as representatives to evaluate the antibacterial activities and mechanism of action by the paper-disk diffusion method and a double fluorescent protein reporter “pDualrep2” system, respectively. A total of 61 isolates exhibited antagonistic activity against the tested “ESKAPE” pathogens, among which 7 strains could produce bioactive metabolites either to be able to block translation machinery or to induce SOS-response in the pDualrep2 system. Notably, Saccharothrix sp. 16Sb2-4, harboring a promising antibacterial potential with the mechanism of interfering with protein translation, was analyzed in detail to gain deeper insights into its bioactive metabolites. Through UPLC-QToF-MS/MS based molecular networking analysis and databases identification, four families of compounds (1−16) were putatively identified. Subsequent bioassay-guided separation resulted in purification of four 16-membered macrolide antibiotics, aldgamycin H (8), aldgamycin K (9), aldgamycin G (10) and swalpamycin B (11), and their structures were elucidated by HR-ESI-MS and NMR spectroscopy. All compounds 8−11 displayed antibacterial activities by inhibiting protein synthesis in the pDualrep2 system. In conclusion, this work demonstrates that Taklamakan desert is a potentially unique reservoir of versatile actinobacteria, which can be a promising source for discovery of novel species and diverse bioactive compounds.